Diversity and Distribution of Ficus (Moraceae) in The Karst Ecosystem of Bantimurung Bulusaraung National Park - Yelastri Yelastri; Sulistijorini Sulistijorini; Nina Ratna Djuita (Universitas Gadjah Mada, 2023)
Bantimurung Bulusaraung National Park is an area that has the largest karst ecosystem in Indonesia. Karst is prone to damage and difficult to reuse, so it requires conservation efforts. One of the plant species that can maintain this sustainability is Ficus which acts as key species in karst ecosystems. However, at this time the species is experiencing disturbances, one of which is due to the experience of invasive plants that can threaten the existence of Ficus because the weeds can colonize habitats and are dominant which can change species diversity. This study aimed to analyze the diversity and distribution of Ficus, compare species composition, and analyze environmental factors that affect Ficus spp. in Pattunuang Resort and Bantimurung Resort. Vegetation analysis method with nesting plots placed by purposive sampling and supported with environmental and soil data measurements to determine the factors that indicate the habitat preference of Ficus. We found 18 plant species of Ficus spp. in total. At Resort Pattunuang we found 14 Ficus species with the highest abundance being Ficus sundaica (27.55%), while we recorded 15 Ficus species at Resort Bantimurung with the highest abundance being Ficus ampelas (29.23%). Ficus species were uniformly distributed with a relatively high ratio of species composition in both resorts. Principal Component Analysis (PCA) showed that the presence of Ficus in Pattunuang Resort is influenced by wind speed, soil temperature, air temperature, soil moisture, soil pH, and air humidity. In Bantimurung Resort, the existence of Ficus is influenced by wind speed, soil temperature, soil moisture, and air humidity.